Origin of natural gases and associated gas hydrates in the Shenhu area, northern South China Sea: Results from the China gas hydrate drilling expeditions. (1st October 2019) - Zhang, Wei; Liang, Jinqiang; Wei, Jiangong; Su, Pibo; Lin, Lin; Huang, Wei
Graphical abstract: Highlights: Thermogenic hydrate gases are recovered in the Shenhu area of the South China Sea. Hydrate gases and deep conventional reservoirs have a paragenetic relationship. Compositional and isotopic fractionation of hydrate gas may occur during migration. Biodegradation of thermogenic gas possibly affect the composition of hydrate gas. Presence of Structure II hydrate expands the base of the gas hydrate stability zone. Abstract: Geochemical data for hydrate gases acquired from the GMGS3 and GMGS4 gas hydrate drilling expeditions conducted by the Guangzhou Marine Geological Survey (GMGS) are used to explore the origin of hydrate gases and their relationship to deep hydrocarbon reservoirs, and to evaluate the contribution of different genetic types of gases to the formation and accumulation of gas hydrates in the Shenhu area of the northern part of the South China Sea (SCS). Compositionally, methane is the dominant gas (>90%) in the void gas and pressure core gas. In addition, as much as ~3% of the gas is composed of C2+ hydrocarbons, including ethane, propane, iso-butane, butane, iso-pentane, and n-pentane. The δ 13 C-CH4 and δD-CH4 values indicate a mixed biogenic-thermogenic origin for the hydrate-forming gas. The methane isotope correlation indicates that the source of the hydrate gas is closely related to the deep conventional gas reservoirs discovered in the Baiyun Sag-Panyu Low Uplift area. Both the hydrate gases and the deep reservoir gases are sourced from the hydrocarbon kitchens in the Baiyun Sag, revealing a paragenetic relationship within the same petroleum system. The composition of the hydrocarbons and the isotopic variation of methane with depth suggest that the thermogenic gas was likely affected by compositional and isotopic fractionation during the long-distance migration from the deep source rocks to the shallow gas hydrate stability zone (GHSZ). The impact of biodegradation on a solely thermogenic gas could also affect the final composition of the hydrate-forming gas. Analysis of the GHSZ based on gas hydrate compositions suggests that the occurrence of thermogenic gas could also indicate the coexistence of structure I (SI ) and structure II (SII ) gas hydrates in the Shenhu area, with the SII hydrates accumulating in or below the lower part of the SI GHSZ. The confirmed presence of SII hydrates in the Shenhu area relocated the base of the GHSZ deeper than was indicated by the bottom simulating reflector, which warrants further study in future explorations for gas hydrates in the Shenhu area.